The level of psychological stress and sleep disorders among people with special needs (the mobility-impaired category) who practice modified physical sports activity - CHENATI, Abdelaziz; NATAH, Kamel (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2024)
This study aimed to identify the degree of psychological stress and sleep disorders among people with special needs (the category of the physically disabled) who practice modified physical and sports activities. It also aimed to reveal the differences between the sample members according to the educational level and age for this type of activity. To achieve the objectives of the study, the appropriate descriptive approach was used for the study, as the researchers designed a questionnaire consisting of 20 statements to measure the degree of psychological stress and sleep disorders applied to a sample of 50 physically disabled individuals distributed according to educational level and age, and using a set of statistical methods. Among the most important results reached by the study are the following: - The degree of psychological stress and sleep disorders among the sample members is average. - There are no statistically significant differences between the sample members attributed to the educational level variable. - There are no statistically significant differences attributed to the age variable. Therefore, attention must be paid to the category of the physically disabled through conducting studies that address several other psychological aspects to understand the condition of this group and work to improve it. It is interested in studying individual sports to understand how the type of sport affects psychological stress and sleep disorders, in addition to the need to design counseling programs to alleviate the degree of psychological stress and sleep disorders and improve their quality of life.